1997
DOI: 10.2527/1997.7541071x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that injection of vitamin A before mating may improve embryo survival in gilts fed normal or high-energy diets.

Abstract: The hypothesis was that administration of vitamin A before ovulation would improve embryo survival in gilts fed a high-energy diet intentionally to reduce embryo survival. Forty crossbred ([Landrace x Large White] x [Duroc x Hampshire]) gilts were fed control (5.5 Mcal ME/d) or high-energy (11.0 Mcal ME/d) diets from 7 d after second estrus until 11 to 12 d after third estrus. Gilts in each dietary group received (i.m.) corn oil or retinyl palmitate (1 x 10(6) IU, vitamin A) on d 15 after second estrus and wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 0 publications
2
20
0
3
Order By: Relevance
“…The oocyte's developmental competence is enhanced by retinoid support during oocyte intrafollicular growth in the cow (Shaw et al, 1995), sheep (Eberhardt et al, 1999), and gilt (Whaley et al, 1997;Whaley et al, 2000), as in rabbits that have high levels of vitamin A (Besenfelder et al, 1996). In agreement with these findings, the addition of 9-cis-RA to in vitro maturation (IVM) cultures stimulated cortical granule migration in bovine oocytes both matured and meiotically arrested for a 24-hr culture period (Duque et al, 2002).…”
Section: Introductionmentioning
confidence: 56%
“…The oocyte's developmental competence is enhanced by retinoid support during oocyte intrafollicular growth in the cow (Shaw et al, 1995), sheep (Eberhardt et al, 1999), and gilt (Whaley et al, 1997;Whaley et al, 2000), as in rabbits that have high levels of vitamin A (Besenfelder et al, 1996). In agreement with these findings, the addition of 9-cis-RA to in vitro maturation (IVM) cultures stimulated cortical granule migration in bovine oocytes both matured and meiotically arrested for a 24-hr culture period (Duque et al, 2002).…”
Section: Introductionmentioning
confidence: 56%
“…Recently, RA treatment during the pre-implantation period in the mouse (Huang et al 2001(Huang et al , 2003 was shown to cause developmental retardation, inhibition of cell proliferation and induction of apoptosis. In previous reports, development of blastocysts to term was not analysed (Shaw et al 1995, Whaley et al 1997, Eberhardt et al 1999, and the precise stage (oocyte, embryo or both) during which retinoids exerted their effects was not determined. Our results involving oocytes isolated by OPU following ROH treatment and subsequently cultured in vitro demonstrate that ROH can influence development by acting on the oocyte during its intrafollicular growth.…”
Section: Embryos Transferred Pregnancy (%)mentioning
confidence: 99%
“…Our results involving oocytes isolated by OPU following ROH treatment and subsequently cultured in vitro demonstrate that ROH can influence development by acting on the oocyte during its intrafollicular growth. In the future, it would be interesting to find out the outcome had the oocyte following ROH treatment been fertilized in vivo and the embryo recovered at specific stages during pre-implantation development, as done in earlier studies (Shaw et al 1995, Besenfelder et al 1996, Whaley et al 1997, Eberhardt et al 1999.…”
Section: Embryos Transferred Pregnancy (%)mentioning
confidence: 99%
See 2 more Smart Citations